Peran Teknologi Finansial Pada Muamalat Din Dalam Persepsi Nasabah Bank Muamalat Ponorogo - Nadila Mei Nur Sholihah; Khoirun Nisak (Falahiya: Journal of Islamic Banking and Finance, 2024)
Introduction: The combination of effectiveness and technology positively impacts society in general due to the problems with Muamalat mobile banking, namely the TIN (Transaction Identification Number), during transactions, which provides sufficient benefits but still causes difficulties for customers. The main aim of this research is to analyze the role of financial technology in Muamalat DIN mobile banking. This research uses field research by looking for data sources directly from Bank Muamalat Ponorogo customers. By using a qualitative research approach. Research Methods: The data collection method used was interviews, with data validity and credibility techniques using triangulation techniques. Results: the results of this research are 1) fintech can provide its role to customers, 2) Factors that Influence Customer Perceptions in Transactions Using Financial Technology (fintech) at Muamalat DIN through 3 aspects, 3) obstacles that customers often face are errors and signals. Conclusion: the role of financial technology (fintech) in Muamalat DIN Ponorogo's mobile banking is sufficient to provide its role to its customers, and there is compatibility through practice in the field with several indicators of financial technology, namely knowledge about financial technology and effectiveness. In providing its role, of course, some factors influence customers' perceptions of making transactions using fintech at Muamalat DIN. Access to use provides convenience. However, there are obstacles for customers, such as application interference, signals that are difficult to reach, etc. Therefore, this is a significant technological obstacle regarding obstacles that customers, such as signal interference, often face.